Evidence for the production and use of Lithoglyphus naticoides beads in Europe during the Holocene: The case of Sultana-Malu Roşu site (Romania). (5th April 2018) - Lazăr, Cătălin; Mărgărit, Monica; Radu, Valentin
Abstract: The ornaments played a significant role in the life of human communities during the Holocene. This paper explores various aspects (with reference to malacology, technology, function, use-wear, art and symbolism) of the perforated shells made of Lithoglyphus naticoides across Europe during prehistory, with a particular focus on the site of Sultana-Malu Roşu (Romania). The assemblages discussed here are dated during the Copper Age (Gumelniţa culture), in terms of absolute chronology the period between 4500 and 3900 cal. BC. The site of Sultana represents an ideal archaeological situation, primarily due to the existence of the pair settlement – cemetery and clear archaeological contexts, but also because it comprises one of the largest amounts of prehistoric L. naticoides ornaments recorded in Europe. Our analysis allowed us to document the collecting techniques, methodology of perforating the shells, type of use, and to evaluate the costs invested in manufacturing these items, based on experimental replication. This enabled us to reconstruct the social expression and symbolism of L. naticoides utilized by past communities in domestic activities or in funeral contexts as part of the construction, affirmation and maintenance of their identity. When these results are compared with data from other sites containing L. naticoides ornaments across Europe, Sultana-Malu Roşu appears unique in its significance as procurement and processing centre for this type of organic raw material.